2019
DOI: 10.3136/fstr.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Date Palm Fruits as a Potential Source of Functional Dietary Fiber: A Review

Abstract: Date palm fruits and their seeds are excellent sources of dietary fiber (DF). Date fruits contain 8.1 -12.7 % Total DFs (of which 84-94 % is insoluble and 6-16 % soluble DF) and is very rich in phenolic antioxidants (1-2 %). Date fruit fibers are composed of cellulose and NSP. Moreover, date DF has important functional properties, such as water-holding capacity and oil-holding capacity. Date seeds contain about 15 % fiber, characterized by a high level of water-insoluble mannan fibers. It has been suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…The diminution of UAC after the thermal treatment concurs with the results of Mrabet et al [7] who found that the UAC of three cultivars was affected by the thermal treatment.…”
Section: Uronic Acids Contentsupporting
confidence: 91%
See 3 more Smart Citations
“…The diminution of UAC after the thermal treatment concurs with the results of Mrabet et al [7] who found that the UAC of three cultivars was affected by the thermal treatment.…”
Section: Uronic Acids Contentsupporting
confidence: 91%
“…In this context, the highest levels of total phenolic and condensed tannins contents were found in methanol:water 80:20 v/v date fruit extracts, while the highest total flavonoid contents and antioxidant activities were found in acetone:water 70:30 v/v [4]. Similarly, extracts obtained from hydrothermally treated date fruits had higher phenolic contents and stronger antioxidant activities [7]. Even though a growing body of literature has highlighted the impact of extraction solvent or the ripening stage on the antioxidant capacities of date fruits, none of them investigated the effect of maturity status and extraction solvent simultaneously on their phenolic pattern, sugar profile and antioxidant capacities.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Consequently, date seeds were suggested to be used in food fortification to enhance their fiber content. The beneficial role of dietary fibers on human health and prevention of cardiovascular disease, diverticulosis, constipation, irritable colon, colon cancer, and positive effects for lowering obesity and blood glucose was previously documented (Al‐Farsi et al., 2007; Mrabet et al., 2019).…”
Section: Resultsmentioning
confidence: 94%